A Network Flow Model for Allocation of Land Uses to Sectors - Bagby, Gordon; Thesen, Arne (Management Science, 1976)
An efficient approach to the problem of minimizing total construction and utility distribution network costs in a region while still meeting projected land use demands is presented. The region is modelled as a directed network with land represented by nodes and utility links by branches. When bounds and costs are placed on levels of land uses and on utility flows in links, the problem becomes a linear programming problem with a special structure. An application of this approach for three utilities and eighty zones is presented together with a discussion on the validity of many assumptions.